You can't scare me! - Stine, R. L. (New York : Scholastic, 2010)
Eddie, tired of show-off Courtney, comes up with a plan to lure her down to Muddy Creek and scare her with the rumors of creepy Mud Monsters, but he makes his first mistake when he refuses to believe the rumors himself.
3.6
5-8
Keywords: Monsters -- Juvenile fiction; Horror stories; Monsters -- Fiction; Horror fiction; Monsters -- Fiction; Horror fiction